The Medium is not the Message: Reconciling Reputation and Free Expression in Cases of Internet Defamation - Danay, Robert (McGill Law Journal / Revue de droit de McGill)

(untitled) (McGill Law Journal / Revue de droit de McGill, 2010)
In this paper the author critiques the approach to defamation over the Internet taken to date by the Canadian common law courts. In the emerging jurisprudence, the courts have relied upon untenably broad generalizations about Internet technology, repeatedly equating it with traditional broadcast media and expressing grave concerns about the corresponding threat to reputation posed by online defamation. This has led the courts to hold that when defamatory words are transmitted using the Internet, this will vitiate the availability of any qualified privilege that would otherwise have immunized the defendant from liability under traditional defamation principles, and substantially increase any resulting award of damages. The author argues that this approach results in a failure to strike the appropriate balance between free expression and the protection of reputation. The jurisprudence can also be seen as a product of a long-standing and unfortunate analytical tendency in defamation law—primarily apparent through the libel/slander distinction—whereby common law courts attach extremely divergent legal consequences to impugned statements based on indefensibly broad generalizations about the degree of danger to personal reputation posed by the medium in which the statement was communicated. Drawing inspiration from a comparison to defamation under the civil law of Quebec, the author proposes a new approach that eschews reliance upon unhelpful analogies and generalizations about particular media including the Internet, and involves the examination of impugned statements on a case-by-case basis, paying careful attention to the context in which these were actually made.